Experimental study on shear strength and creep properties of loess modified by microbially induced calcium carbonate precipitation (MICP) under freeze-thaw cycles - Jiaming Liu; Zhanyuan Zhu; Junlin He; Fei Luo; Yuping Yang; Huawei Gu; Zhuoying Wang (Case Studies in Construction Materials)
Numerous loess relic sites with cultural and historical values exist in the seasonally frozen ground region of Northwest China. Freeze-thaw action is an essential factor in inducing cracking and collapse of loess relic sites, and the creep behavior of loess also affects its long-term stability. Microbially induced calcium carbonate precipitation (MICP) technology has a promising application in earthen ruin reinforcement due to its environmental friendliness and good compatibility. To evaluate the feasibility of MICP technology for reinforcing loess relic sites in the seasonally frozen ground, triaxial compression tests, triaxial creep tests, and SEM tests were conducted on MICP modified loess after 0, 1, 3, 7, and 9 freeze-thaw cycles. Then, the changing laws of shear strength and creep properties of samples in the freeze-thaw conditions were analyzed. The results show that the MICP technology can enhance the mechanical properties and frost resistance of loess. The shear strength, cohesion, and long-term strength of MICP modified loess are enhanced by 27.8 %, 109 %, and 29.8 %, respectively, under 100 kPa confining pressure, and their reduction is smaller than that of the untreated loess after 9 freeze-thaw cycles; the internal friction angle fluctuates within 1°. Finally, the reinforcement mechanism and freeze-thaw resistance mechanism of MICP technology were revealed. Microbially induced calcium carbonate can cement soil particles, fill interparticle pores, and inhibit the development of pores and cracks caused by freeze-thaw action. The results can provide a theoretical foundation and scientific basis for the long-term stability analysis of loess relic sites reinforced with MICP technology.